Desain Model dan Materi Pembelajaran Berbasis Teknologi Informasi - Ali Rahman (IAIN PAREPARE, 2018)
ABSTRACTICT is one of the learning media that is widely used in various fields of educationbecause it increases the effectiveness and efficiency in the learning process. Theuse of ICT in learning includes tutorials, application tools and communication,while the application of ICT in the world of education is in the form of electronicbooks and e-learning. The use of information and communication technology ineducation is absolutely necessary to answer problems in the education sector,especially for access and equity and the quality of education. Everything will runsmoothly depending on the technology and network conditions available.Standardization and utilization of ICT in education is very important to ensure thequality of educational processes and outcomes. Teachers as implementers ofeducation are required to design the learning process by presenting the rightlearning atmosphere so that the learning process can take place effectively,efficiently and pleasantly. One learning model that can be used as a reference formodel design and learning based material is the ADDIE model.